Local Wisdom-based Contextual Learning as Embedded-STEM approach in High School Chemistry - Anugrah, Indah Rizki; Kartimi, Kartimi (IJIS Edu : Indonesian Journal of Integrated Science Education, 2022)
The application of STEM in Indonesia can be made through an embedded approach using the social, cultural and technological contexts encountered by students daily. This study aimed to reconstruct the context of Cirebon local wisdom, i.e. batik, to be used as a context for embedded STEM chemistry learning in high school. This research used a qualitative method by choosing the Model of Educational Reconstruction (MER) as the research framework. In this study, observations were made on the batik-making process, a literature review to explore the batik context's chemical perspective, and interviews to obtain information about students' preconceptions about batik. The findings indicated that the essential components of batik (fabric, wax, and dye) and the process of batik making were inextricably linked to chemical processes. According to the literature review, the context of batik is connected to several high school chemistry concepts, including organic chemistry (particularly regarding aromatic derivatives and polymers), electromagnetic radiation, chemical bonds, acid-base, oxidation and reduction, and stoichiometry. Meanwhile, it is known from student interviews that students' preconceptions about the scientific content of batik and related chemical concepts remain clearly distinguishable from their correct scientific conceptions. However, students expressed a favourable attitude toward the possibility of incorporating batik into chemistry instruction